Performing al-Andalus : Music and Nostalgia across the Mediterranean - Shannon, Jonathan Holt (Book collections on Project MUSE., 2015)
Performing al-Andalus explores three musical cultures that claim a connection to the music of medieval Iberia, the Islamic kingdom of al-Andalus, known for its complex mix of Arab, North African, Christian, and Jewish influences. Jonathan Holt Shannon shows that the idea of a shared Andalusian heritage animates performers and aficionados in modern-day Syria, Morocco, and Spain, but with varying and sometimes contradictory meanings in different social and political contexts. As he traces the movements of musicians, songs, histories, and memories circulating around the Mediterranean, he argues that attention to such flows offers new insights into the complexities of culture and the nuances of selfhood.